Freeze-dried snacks obtained from frozen vegetable by-products and apple pomace – Selected properties, energy consumption and carbon footprint - Karwacka, Magdalena; Ciurzyńska, Agnieszka; Galus, Sabina; Janowicz, Monika (Innovative food science & emerging technologies, 2022)
Valorisation of food waste is one of the goals that food industry needs to achieve in terms of sustainable development. The aim of the research has been to analyse selected properties of freeze-dried vegetable snacks obtained from wholesome waste derived from the fruit and vegetable industry, such as frozen vegetable by-products and apple pomace as well as to estimate carbon footprint as the technological process output on the basis of the energy used for the purpose of producing snacks. Properties of snacks, such as water content and activity, shrinkage, density, porosity and hardness, were determined using common methodology. The water content of the finished products was very low (<1.5%) and determined the water activity below 0.02. Technological operations, such as grinding, caused destruction of the cell structure of the ingredients, which subsequently made the product structure inhomogeneous and more dense than most of the freeze-dried plant tissues. The snacks were porous and featured by hardness of 79.43–113.26 N. The colour depended on their composition, and freeze-drying caused the products to brighten significantly. The estimated carbon footprint (CF) depended on the technological process. Freeze-drying had the most significant impact upon the CF, accounting for 86–87%. The use of apple pomace powder as a structure- and texture-forming additive constitutes the subject matter representing great prospects for further research. •Food waste and by-products can be used as raw material to manufacture new products.•Structure of the snacks was disordered and fragile.•Freeze drying was the factor with the greatest impact on energy consumption and CF.